2005
DOI: 10.1128/iai.73.10.6210-6219.2005
|View full text |Cite
|
Sign up to set email alerts
|

TheSalmonella entericaSerovar TyphitsxGene, Encoding a Nucleoside-Specific Porin, Is Essential for Prototrophic Growth in the Absence of Nucleosides

Abstract: The Salmonella enterica serovar Typhi tsx gene encodes a porin that facilitates the import of nucleosides. When serovar Typhi is grown under anaerobic conditions, Tsx is among the outer membrane proteins whose expression increases dramatically. This increase in expression is due, at least in part, to increased transcription and is dependent on Fnr but not on ArcA. A mutant derivative of serovar Typhi strain STH2370 with a deletion of the tsx gene is an auxotroph that requires either adenosine or thymidine for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 71 publications
0
23
0
Order By: Relevance
“…In contrast, in three independent isolates of S. Typhi, a Dtsx nonpolar mutation confers an auxotrophic requirement for the nucleosides adenosine or thymidine (Bucarey et al 2005).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…In contrast, in three independent isolates of S. Typhi, a Dtsx nonpolar mutation confers an auxotrophic requirement for the nucleosides adenosine or thymidine (Bucarey et al 2005).…”
Section: Resultsmentioning
confidence: 93%
“…Previously, we have shown that complementation of an S. Typhi Dtsx mutant with a derivative of the moderate-copy-number plasmid pSU19 carrying the cloned tsx gene yields a strain that is prototrophic, yet cannot grow in the presence of high concentrations of adenoside or thymidine, suggesting that overproduction of the Tsx porin results in an imbalance of membrane proteins that renders S. Typhi sensitive to adenosine or thymidine (Bucarey et al 2005). This is the same phenotype exhibited by the S. Typhi DimpX mutant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The loss of classical porin expression in gram-negative pathogens often results in decreased fitness in both in vitro and in vivo environments (1,6,(8)(9)(10)41). However, 35000HP:: P2AB did not exhibit any loss of viability or demonstrate any growth defect in vitro or in vivo in the human challenge model (20).…”
Section: Discussionmentioning
confidence: 99%